2020
DOI: 10.4149/neo_2018_181129n908
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circHIPK3 serves as a prognostic marker to promote chronic myeloid leukemia progression

Abstract: Increasing evidence demonstrate that circular RNAs (circRNAs) play critical role in regulation of gene expression, which participate in the pathogenesis of cancer, including chronic myeloid leukemia (CML). In this study, we aimed to investigate the expression profiling of circHIPK3 in CML. We found that circHIPK3 was significantly upregulated in peripheral blood mononuclear cells (PBMC) and serum samples from CML compared with healthy controls. High circHIPK3 expression predicted a poor outcome of CML patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 16 publications
(21 reference statements)
1
22
0
Order By: Relevance
“…Circ_0075001 was overexpressed in M0 or M1 subtype of AML patients and significantly downregulated in M2, M4 and M5 subgroups, showing the potential to distinguish the differentiation degree of the AML [107]. The high expression of circHIPK3 in serum of CML patients was related to Sokal relative risk, an independent factor of CML prognosis, and shorter OS, indicating poor clinical outcome [70]. The level of circ-RPL15 was negatively correlated to the mutation state of immunoglobulin heavy chain (IGHV) gene, predicting poorer OS [108].…”
Section: Promising Biomarkers For Diagnosis and Prognosismentioning
confidence: 92%
See 2 more Smart Citations
“…Circ_0075001 was overexpressed in M0 or M1 subtype of AML patients and significantly downregulated in M2, M4 and M5 subgroups, showing the potential to distinguish the differentiation degree of the AML [107]. The high expression of circHIPK3 in serum of CML patients was related to Sokal relative risk, an independent factor of CML prognosis, and shorter OS, indicating poor clinical outcome [70]. The level of circ-RPL15 was negatively correlated to the mutation state of immunoglobulin heavy chain (IGHV) gene, predicting poorer OS [108].…”
Section: Promising Biomarkers For Diagnosis and Prognosismentioning
confidence: 92%
“…CircHIPK3 could downregulate miR-421, leading to the increased FOXO3a expression, thereby inhibiting pyroptosis and releasing IL-1β and IL-18 [69]. Previous studies have found that the high expression of circHIPK3 in CML was significantly associated with poor prognosis [70]. Besides, AKT/FOXO3a pathway was involved in the apoptosis of AML [71].…”
Section: Regulating Pyroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Induced circHIPK3 expression predicted a poor outcome of CML patients, and circ_100053 might be associated with imatinib resistance in CML. 235,236 In addition, circ_0080145 was found to be up-regulated in CML, and silence of circ_0080145 significantly inhibited cell proliferation of CML by sponging miR-29b. 237 Taken together, circRNAs were distributed broadly in myeloid leukemia, and abnormal expressions of circRNAs were closely related to the progression and tumorigenesis of myeloid leukemia including AML and CML.…”
Section: Myeloid Leukemiamentioning
confidence: 96%
“…[8][9][10][11][12] Previous studies have shown that circHIPK3 spongs miR-145-5p, miR-124, miR-558, miR-637, miR-193a, miR-338-3p, and miR-637 to regulate oxaliplatin-resistance, proliferation, tube formation, invasion, autophagy, migration, and apoptosis in lung cancer, preeclampsia, gastric cancer, colorectal cancer, chronic myeloid leukemia, bladder cancer, prostate cancer. [13][14][15][16][17][18][19][20] However, the role and function of circHIPK3 have not been revealed in PC.…”
Section: Introductionmentioning
confidence: 99%